PENGGUNAAN TEKNOLOGIÂ BAR-CODE UNTUK MENURUNKAN KESALAHAN DALAM PEMBERIAN OBAT - Zakiyah, Ana (JURNAL KEPERAWATAN SEHAT, 2012)
AbstractThe development of information technology has penetrated the world of health and can be applied to services provided in the hospital one of which is the administration of drugs. Over recent years, the incidence of medication errors are common and cause of 7000 deaths in the U.S. This barcode is a system that has been proven to reduce errors in drug administration by 50%. Effectively using the system is able to identify errors during the medication administration process. Barcode system is also the best technology solutions to improve pharmacy and nursing communication, keeping nursing satisfaction by minimizing the additional workload, identifying persistent in order to facilitate a proactive approach to prevent medication errors. Electronic Medical Record (EMR) including the electronic medication administration record (Emar), is an important component as it is the good process is also required CPOE (Computerized prescriber order entry).